2013
DOI: 10.1590/s2176-94512013000200023
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the soft tissue of young Japanese-Brazilian, Caucasian and Mongoloid patients

Abstract: Objective: To determine the normality mean values in the soft tissue cephalometric measurements of young Japanese-Brazilian, with normal occlusion and compare the results of the variables with compatible samples of young Caucasians and Mongoloids. Methods: Forty radiographs of young Caucasians, 32 of Japanese-Brazilians and 33 of Mongoloids were used. The three samples presented individuals with normal occlusion and well-balanced face. The samples were divided by gender due to the soft tissue characteristics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…Ruiz [23] estimated facial soft tissue thickness at 17 anatomical landmarks of Columbian adults and found no sexual dimorphism in FSTT, though midline landmarks showed some differences. Fernandez et al [24] conducted a comparative study of soft tissue thickness in Japanese, Mongoloids and Caucasoid subjects and found significant differences between two sexes and in different races at different anthropological facial landmarks.…”
Section: Discussionmentioning
confidence: 99%
“…Ruiz [23] estimated facial soft tissue thickness at 17 anatomical landmarks of Columbian adults and found no sexual dimorphism in FSTT, though midline landmarks showed some differences. Fernandez et al [24] conducted a comparative study of soft tissue thickness in Japanese, Mongoloids and Caucasoid subjects and found significant differences between two sexes and in different races at different anthropological facial landmarks.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the advancement of cephalometrics, it has been established that there are differences in FSTT in different ethnic groups, which means that one standard of facial esthetics may not be applied to other ethnic groups. Therefore, researchers have compared the cephalometric characteristics of different races with the established standard of Caucasian Americans, to establish specific cephalometric values of FSTT for different ethnic groups [ 8 , 11 , 12 ]. Furthermore, age [ 3 , 13 , 14 ], sex, ethnicity [ 3 , 15 ], climate [ 16 ], activity, obesity and the body mass index (BMI) [ 17 – 19 ] of individuals have a significant influence on this relationship, together with other conditions.…”
Section: Introductionmentioning
confidence: 99%
“…One must also take into account each individual's ascendency 19,25 , as there are differences in dentofacial relationship depending on the ethnic variability of each racial group 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors consider a limitation of this study the fact that the ancenstry of each individual included in the sample was not determined and evaluated as there are differences in the dentofacial relationship depending on the ethnic variability of each racial group 19,25 .…”
Section: Discussionmentioning
confidence: 99%